Hypolipidemic activity of Hiptage benghlensis leaf extracts on high fat diet induced hyperlipidaemic rats (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
The present study was designed to evaluate the hypolipidemic effects of aqueous extract (HBAE) and ethanolic extract (HBEE) of leaves of Hiptage benghalensis by using high-fat-diet induced hyperlipidemic animal model. Albino male Wistar rats (120-150 g) were split into various groups, each of which had six individuals. Normal rats (group I) were received 0.3% Carboxy methyl cellulose (CMC) with standard laboratory diet, while hyperlipidemic rats (group II, III, IV, V, VI and VII) were fed high fat diet for induction of hyperlipidemia. Hyperlipidaemic control group (group II) received 0.3% CMC (10 ml/kg/day), standard group (group III) received gemfibrozil (50 mg/kg/day, p.o.), HBAE groups (group IV and V) received aqueous extract of Hiptage benghalensis (100 and 200 mg/kg/day, p.o.), and HBEE groups (group VI and VII) received ethanolic extract of Hiptage benghalensis (100 and 200 mg/kg/day, p.o.), concurrent with high fat diet for consecutive four weeks. The HBAE and HBEE treatments led to significant (P < 0.05) reduction in serum lipids (TC, TG, LDL and VLDL) and elevation in cardio protective HDL, when compared to hyperlipidaemic rats (group II). Phytochemical screening revealed the presence of phytoconstituents such as alkaloids, flavonoids, saponins, tannins, phenolic compounds and steroids, which may be attributed to observed hypolipidemic effects. The findings of the present study concluded that HBEE (200 mg/kg, p.o.) had potent hypolipidemic effects.